Silencing of lipocalin-2 and its receptor improved cardiomyocytes viability via decreasing iron uptake, mitochondrial fission, mitophagy and apoptosis under iron overload condition. (25th November 2020) - Kumfu, S; Chattipakorn, S.C; Chattipakorn, N
Abstract: Background: Iron overload cardiomyopathy is a common cause of death in iron overload patients. L-type calcium channels (LTCC) and T-type calcium channels (TTCC) have been shown to play important roles for iron uptake into the heart under iron overload condition. Recently, cardiomyocytes which exposed to lipocalin-2 (LCN-2) have been shown to increase apoptosis due to excessive intracellular iron accumulation. However, the mechanistic roles of LCN-2 and LCN-2 receptor (LCN-2R) as iron transporters in cardiomyocytes under iron overload condition have never been investigated. Purpose: We hypothesized that the LCN-2 and LCN-2R are alternate iron uptake pathways into cardiomyocytes under iron overload condition. Methods: H9c2 cardiomyocytes were treated with either LCN-2 siRNA or LCN-2R siRNA for 72 hr or LTCC blocker (verapamil), TTCC blocker (TTA-P2), or iron chelator deferiprone (DFP) for 1 hr. After treatment, cells were exposed to ferric ammonium citrate (FAC, Fe3+) or FAC + 1mM ascorbic acid (Fe2+) at 200 μM for 48 hr. Intracellular iron level, cell viability, mitochondrial dynamics, mitophagy and apoptosis were determined. Results: Both Fe2+ and Fe3+ treated groups showed significantly increased intracellular iron uptake, decreased cell viability, increased mitochondrial fission, mitophagy and apoptotic protein expression in cardiomyocytes. Under Fe2+ overload condition, treatments with LTCC blocker, TTCC blocker, and DFP could significantly decrease intracellular iron accumulation and increase cell viability via decreasing mitochondrial fission, mitophagy and cleaved caspase-3 (Figure), whereas both LCN-2 and LCN-2R siRNA treatment had no beneficial effects on these parameters. Under Fe3+ overload condition, treatment with LCN-2 siRNA, LCN-2R siRNA, and DFP showed beneficial effects on those parameters, whereas neither LTCC nor TTCC blocker provided these benefits (Figure 1). Conclusion: Silencing of LCN-2 and LCN-2R increased cardiomyocyte viability via decreasing iron uptake, mitochondrial fission, mitophagy and apoptosis under Fe3+ iron overload condition. Meanwhile, treatment with calcium channel blockers improved cardiomyocytes viability via decreasing iron uptake, mitochondrial fission, mitophagy and apoptosis under Fe2+ iron overload condition. All of these findings suggested that LTCC and TTCC played important roles for Fe2+ uptake, whereas LCN-2 and LCN-2R were essential for Fe3+ uptake into the cardiomyocytes under iron overload conditions. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Thailand Research Fund and NSTDA Research Chair Grant (NC)